2014
DOI: 10.2519/jospt.2014.5249
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Plane Trunk Posture Influences Patellofemoral Joint Stress During Running

Abstract: Study Design Cross-sectional, repeated-measures. Objectives To examine the association between sagittal plane trunk posture and patellofemoral joint (PFJ) stress, and to determine whether modifying sagittal plane trunk posture influences PFJ stress during running. Background Patellofemoral pain is the most common injury among runners and is thought to be the result of elevated PFJ stress. While sagittal plane trunk posture has been shown to influence tibiofemoral joint mechanics, no study has examined the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 42 publications
8
93
1
Order By: Relevance
“…between PFJ stress and trunk flexion in healthy individuals during running tasks. 93 While caution should be placed in comparing relationships between the trunk and knee across pathologies and in a healthy population, it does present with the possibility to provide insight into this altered movement in individuals with PFP.…”
Section: Trunkmentioning
confidence: 98%
“…between PFJ stress and trunk flexion in healthy individuals during running tasks. 93 While caution should be placed in comparing relationships between the trunk and knee across pathologies and in a healthy population, it does present with the possibility to provide insight into this altered movement in individuals with PFP.…”
Section: Trunkmentioning
confidence: 98%
“…In the context of running in participants with PFPS, changes to VARelements might relate to the loads that are applied to soft tissues during different movement phases. For instance, VARelements may be reduced during the initial or final sub-phase of stance (Hamill et al 1999;Heiderscheit et al 2002) as this is when most stress is applied to the patellofemoral joint and is likely to be most painful (Teng and Powers, 2014). This implies that during chronic pain, changes to VARelements depend on the effect on pain/pathology and function.…”
Section: Altered Varelements For Some Features Of Movement But Not Omentioning
confidence: 99%
“…Sample size was based off previous repeated measure studies that focused on PF kinetics and kinematics. [12][13][14]19 All participants included were rearfoot strikers, as determined by center of pressure at initial contact occurring in the rear most third of the foot during testing. 18 Additional inclusion criteria included five years of recreational running experience, self-reported running routine of >10 miles per week, and a score of at least level five on the Tegner Activity Level Scale (a questionnaire of regular participation with recreational sports which require running).…”
Section: Subjectsmentioning
confidence: 99%
“…16,17 Conservative intervention strategies of PFP often involve attempts to alter running mechanics. 12,13,16 Decreasing step length by 10% results in a 15-20% decrease in patellofemoral joint (PFJ) kinetics, 16 while increasing the runner's cadence by 10% was successful in reducing PFJ forces by 14%. 12 Teng and Powers reported that a 7 degree increase in trunk flexion led to significant decreases in knee extensor energy absorption and generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation